FAKTOR â FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR - Novitasari, Cahyaning; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTCapital structure is the comparison between foreign capital and own capital. capital structure is the most important matter in the making of funding decision in order to make the company can maintain their optimum capital structure to minimize capital cost. This research is meant to test the influence of Return on Investment, Return on Equity, assets structure, liquidity, growth in sales and taxes on capital structure manufacturing company. Companies that made the object of this research is a manufacturing company in the field of metal sub-sectors listed on Indonesia Stock Exchange during the period of 2013-2015 which is consist of 10 companies. So the research sample become 30. Based on the results of the feasibility tests models known that the independent variables GCC consists of Return on Investment, Return on Equity, Assets Structure, Liquidity, Growth in Sales and Taxes have an influence to the capital structure. Based on the t test results showed that the Return on Investment (ROI) and Liquidity (CR) are significant influence negatively to the capital structure of the company. Return on Equity (ROE), structure assets and tax has no consequences on the companyâs capital structure. While sales growth has positive effect on the capital structure.Keywords: return on investment, return on equity, liquidity, assets structure, sales growth